1990
DOI: 10.3102/00346543060004531
|View full text |Cite
|
Sign up to set email alerts
|

Phases of Meaningful Learning

Abstract: The research literature is examined for evidence suggesting that in complex, meaningful learning the learner passes through a series of stages or phases during which the learning process and the variables influencing it change systematically. After discussing various conceptual and methodological issues, phase theories in both simpler and more meaningful forms of learning are reviewed. Finally, the initial, intermediate, and terminal phases of learning are discussed. It is suggested that during the initial pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(98 citation statements)
references
References 29 publications
3
90
0
1
Order By: Relevance
“…This proposition is supported by the view that the kind of activities and interactions in which we engage (i.e. the things we do) influence how we think, act and learn (Billett 1996, Rogoff and Lave 1984, Shuell 1990, Van Lehn 1998. Consequently, different outcomes will likely result from learning vocational tasks in an environment that provides authentic vocational experiences (e.g.…”
mentioning
confidence: 62%
“…This proposition is supported by the view that the kind of activities and interactions in which we engage (i.e. the things we do) influence how we think, act and learn (Billett 1996, Rogoff and Lave 1984, Shuell 1990, Van Lehn 1998. Consequently, different outcomes will likely result from learning vocational tasks in an environment that provides authentic vocational experiences (e.g.…”
mentioning
confidence: 62%
“…• Learning is a process of constructing personal meaning or "'sense making'" (Shuell, 1990;Marzano, 1992;Gagn6, 1985): individual learners actively seek to understand their environment--the content of the school's curriculum, for example. Such meaning will be highly personal, and students may develop very different understandings of the same curriculum's content.…”
Section: Assumptions About the Learning Processmentioning
confidence: 99%
“…These researchers have found that higher level learning occurs when students are engaged in authentic tasks that are socially mediated by experts in that task. Shuell (1990) points out that prior experience with procedural and contextual features of the task enhances understanding and contributes to motivation, but that novices generally confront new information or processes without cognitive or social involvement. Accordingly, many students who study new concepts and theories for the first time view them as facts to be memorized, unless the setting requires some interaction with the material (Cognition and Technology Group, 1990).…”
Section: Introductionmentioning
confidence: 98%